Uji Aktivitas Teh Celup Fraksi Metanol Rimpang Temu Mangga (Curcuma mangga Valeton and Zijp) sebagai Antihiperlipidemia - Dyan Fitri Nugraha; Noval Noval; Kunti Nastiti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The high number of deaths from cardiovascular disease in the world makes cardiovascular drugs, such as antihyperlipidemic or dyslipidemia often used by patients in the whole world. Statins are first-line drugs that are often used, but have various side effects, such as myalgia, rhabdomyolysis, and are considered to trigger diabetes mellitus. Meanwhile, the use of traditional medicines such as the Temu mangga’s rhizome (Curcuma mangga Valeton and Zijp) is often used by the community as antihyperlipidemic therapy. The purpose of this study was to scientifically prove the antihyperlipidemic activity of teabags from the methanol fraction of Temu Mangga’s rhizome in reducing lipid profiles, namely total cholesterol, triglycerides, and LDL, as well as increasing HDL. This research method is experimental by measuring the parameters of total cholesterol, triglycerides, LDL, and HDL as well as the bodyweight of the test animals as additional parameters. The test group was divided into 3 doses, namely 0.35 mg, 0.7 mg, and 1.4 mg per 200 grams of test animals. The results showed that there was no significant difference between all groups, both in lipid profile and bodyweight of the test animals. However, a dose of 1.4 mg had better triglyceride lowering activity than the positive control, and the activity of the methanol fraction of the Temu Mangga’s rhizome was predicted to be similar to statins.